Animals have expanded the evolutionary legacy of unicellular ancestors in blood cells - Yosuke Nagahata; Yuji Nishimura; Ryota Kaitani; Jason Cheok Kuan Leong; Izumi Oda-Ishii; Hisanori Kohtsuka; Shinya Abe; Tasuku Ishida; Marina Carmona-Rivas; Sebastian R. Najle; Elena Casacuberta; Koichi Ikuta; et al. (Proceedings of the National Academy of Sciences, 2026)
Blood cells are common and unique to animals, enabling them to address critical challenges of defense and transport. Thus, their evolution represents a defining innovation in metazoan multicellular life. However, their evolutionary trajectory about how blood cells emerged and diversified throughout animal history remains unclear. Here, we present a combination of bioinformatics and functional data that demonstrate that the metazoan blood cell program most likely originated through the repurposing of an ancestral premetazoan toolkit governed by Fos . This primordial program established the macrophage-like initial blood cells at the metazoan root. Then, the first lineage bifurcation at the origin of Bilateria drove the emergence of a specialized mast/killer lineage, characterized by acquisition of granular proteases for antiparasitic defense. Subsequent deuterostome/vertebrate innovations branched T/NK and erythrocyte/thrombocyte lineages from mast cells while B cells derived from macrophages. Our data also show that a prototypic thymus formed at the gill edges of a chordate ancestor. In line with the evolutionary history, the modern hematopoietic pathway shows a vestige of the phylogeny; differentiation potentials of phylogenetically old cell lineages expressing Fos such as macrophages and mast cells are widely retained, and ancient HSCs with limited lineage potentials have been inherited as origo-lineage progenitors. Our framework provides the history of blood cells showing an adaptive innovation built upon ancient unicellular foundations.